Improve survival of mango at establishmentby hydrogel polymer incorporation - Iberahim, Ismail; Ismail, Razi; Sugip, Fauzirom (2001)
The application of hydrogel polymer into the soil provide opportunity to reduce the frequency of irrigation. The mango plants incorporated with hydrogel delay the effect of drought stress. Eventhough stomatal conductance. photosynthesis rate and leaf water potential of hydrogel polymer treatment were slightly similar with water stress plants but the plants were still showed turgirdity and did not show any sign of water stress with hydrogel incorporation.